Job Satisfaction Impact on Employee Performance at the Solok Regency Transportation Service - Farhan Hidayatul Fajri; Afni Yeni; Seflidiana Roza (Journal of Behavioral Economics, Finance, and Management Insights, 2025)
The research was carried out in order to address worries over different levels of employee productivity and the necessity to comprehend the impact of internal elements like leadership, motivation, and job contentment within the Solok Regency Transportation Department. The primary goal of this study is to assess how leadership, motivation, and job satisfaction affect the performance of employees at the Solok Regency Transportation Department (DISHUB). The focus of the study includes DISHUB employees situated on Jl. Raya Koto Baru, Solok Regency, West Sumatra. The study utilised quantitative research by distributing questionnaires to 92 employees for data collection. Findings indicated that leadership did not have a significant impact on employee performance, with a t-count value of 1.294 and a significance level of 0.200. Similarly, motivation did not show a significant effect, with a t-count of -1.873 and a significance of 0.065. On the other hand, job satisfaction was found to have a notable influence on employee performance, with a t-count of 2.060 and a significance of 0.043. Moreover, the three variables collectively affected employee performance, as evidenced by an F-count of 3.230 and a significance level of 0.027. The coefficient of determination (R²) suggested that 11.9% of the variation in employee performance stems from leadership, motivation, and job satisfaction, with the remaining influenced by other factors. The study offers suggestions for enhancing employee job satisfaction to boost overall performance within the organisation.